Water dynamics in cement paste at early age prepared with pozzolanic volcanic ash and Ordinary Portland Cement using quasielastic neutron scattering. (August 2016) - Kupwade-Patil, Kunal; Tyagi, Madhusudan; Brown, Craig M.; Büyüköztürk, Oral
Abstract: Early age hydration kinetics of Portland cement with pozzolanic volcanic ash was examined using quasielastic neutron scattering. Volcanic ash consisting of two different particle sizes was used to prepare cement pastes with different ratios of Portland cement to volcanic ash. The concentration of the volcanic ash played a major role in the bound water index and self-diffusion coefficients of hydration water confined in the cement paste. An increase in the particle size of the volcanic ash affected the degree of hydration by allowing more free and mobile water in the gel pores, suggesting that volcanic ash may not have completely reacted during the experimental time frame. This study shows that the particle size along with variation in volcanic ash composition governs the early age hydration process in volcanic ash cements.